2015
DOI: 10.1080/01652176.2015.1096429
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence of biofilm-producingStaphylococcus pseudintermediusisolated from healthy dogs in South Korea

Abstract: Background: Staphylococcus pseudintermedius is a common bacterial pathogen in dogs with pyoderma, otitis externa, and wound infection. Objective: The purpose of this study was to evaluate the biofilm-producing ability for methicillin-resistant (MRSP) and methicillin-susceptible (MSSP) S. pseudintermedius isolates from healthy dogs. Animals and methods: Ninety-two isolates, consisting of 40 MRSPs and 52 MSSPs, were included in the study. Biofilm production was determined using a quantitative adherence assay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Thus, a significant difference in the prevalence of strong or moderate biofilm production was observed between mammalian-origin MR and MS CoNS (P < 0.001, independent t test). This finding differs from observations on MR and MS Staphylococcus pseudintermedius isolated from companion dogs in Republic of Korea, indicating no difference of biofilm-producing abilities between MR and MS S. pseudintermedius [16]. In birds, 96.4% (54/56) CoNS could form biofilm regardless of methicillin resistance, and 62.5% (35/56) of the CoNS demonstrated strong or moderate biofilm production ability.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…Thus, a significant difference in the prevalence of strong or moderate biofilm production was observed between mammalian-origin MR and MS CoNS (P < 0.001, independent t test). This finding differs from observations on MR and MS Staphylococcus pseudintermedius isolated from companion dogs in Republic of Korea, indicating no difference of biofilm-producing abilities between MR and MS S. pseudintermedius [16]. In birds, 96.4% (54/56) CoNS could form biofilm regardless of methicillin resistance, and 62.5% (35/56) of the CoNS demonstrated strong or moderate biofilm production ability.…”
Section: Resultscontrasting
confidence: 92%
“…Most of the CoNS isolated from wild animals were capable of biofilm production, with 65.1% being classified as either strong or moderate biofilm producers. This data indicates relatively lower prevalence of biofilm producing CoNS in wild animals than in companion animals [1618]. However, considering that all wild animals evaluated in this study seem to have no prior exposure to antibiotic therapy, this prevalence indicates a wider spread of the biofilm-producing bacteria in the environment.…”
Section: Resultsmentioning
confidence: 80%
“…The ability of S. pseudintermedius to produce biofilms has been previously reported. In Japan, all S. pseudintermedius isolates were able to produce biofilm [ 17 ], while in South Korea, a biofilm-forming quantitative assay showed that all S. pseudintermedius isolates produced either strong or moderate biofilm [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that MRSP‐ST71 can produce biofilms, suggesting the necessity of investigating the prevalence of biofilm‐producing S. pseudintermedius and their implications on AMR in veterinary medical practices (Dicicco et al, 2012 ; Osland et al, 2012 ; Singh et al, 2013 ). The icaA and icaD genes responsible for biofilm production were detected among healthy dogs' isolates in one study (Han et al, 2015 ).…”
Section: Main Findings and Discussionmentioning
confidence: 99%